2007
DOI: 10.1523/jneurosci.2311-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of Variability in Saccadic Eye Movements

Abstract: Our movements are variable, but the origin of this variability is poorly understood. We examined the sources of variability in human saccadic eye movements. In two experiments, we measured the spatiotemporal variability in saccade trajectories as a function of movement direction and amplitude. One of our new observations is that the variability in movement direction is smaller for purely horizontal and vertical saccades than for saccades in oblique directions. We also found that saccade amplitude, duration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(163 citation statements)
references
References 58 publications
(92 reference statements)
11
146
3
Order By: Relevance
“…Another study based on the covariances between saccade endpoints and kinematic properties of the movement found that a large portion of end-point variance in saccades is indeed due to target localization errors, not motor noise (van Beers, 2007). This last study found, however, a stronger contribution of motor noise compared with the result reported here.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Another study based on the covariances between saccade endpoints and kinematic properties of the movement found that a large portion of end-point variance in saccades is indeed due to target localization errors, not motor noise (van Beers, 2007). This last study found, however, a stronger contribution of motor noise compared with the result reported here.…”
Section: Discussioncontrasting
confidence: 68%
“…l (t) corresponds to the localization error of target T, as a result of sensory noise and/or an imperfect sensory-motor transform of the sensory input into a motor command. Errors in localization of the target largely contribute to the variability of saccadic eye movements and exceed the motor noise (van Beers, 2007). However, contrary to motor noise, these errors can be predicted from the efferent motor commands.…”
Section: E)mentioning
confidence: 99%
“…There are many sources of variability in human goaldirected movements (van Beers 2007), and it seems safe to assume that people will try to move in a way that will minimize the detrimental effects of such variability (van Beers 2008;Brenner and Smeets 2007;Harris and Wolpert 1998;Müller and Sternad 2004;Trommershauser et al 2003). An obvious way to do so is by minimizing the variability itself, for instance by moving slowly.…”
Section: Introductionmentioning
confidence: 99%
“…A luminance change detection task ensured the proper accuracy of the fixations. The raw eye-tracker output was then least-squares fitted to horizontal and vertical eye orientations using two biquadratic equations (Bonnetblanc and Baraduc, 2007;van Beers, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Actually, the contribution of visual noise to saccade endpoint variance increases with target eccentricity (van Beers, 2007;Morel and Baraduc, 2010). We would hence expect a decrease of visual weight with T1 eccentricity.…”
Section: Optimal Integration Of Target and Background Information Optmentioning
confidence: 99%